2011
DOI: 10.1111/j.1600-0536.2011.01945.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensitization and elicitation responses caused by mixtures of common fragrance allergens

Abstract: Our findings suggest that mixtures of allergens increase the primary response that potentiates the generation of memory T cells in response to the specific allergen. Thus, allergen mixtures enhance both induction and elicitation of contact allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
6

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 16 publications
1
59
0
6
Order By: Relevance
“…A recent study by Bonefeld et al (33) has indeed shown that mixtures have increased potency in sensitization and the elicitation of contact allergic reactions as compared with isolated fragrance allergens. These results may explain why fragrance allergy is a prevalent phenomenon in spite of the fact that many fragrance allergens are categorized as weak sensitizers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Bonefeld et al (33) has indeed shown that mixtures have increased potency in sensitization and the elicitation of contact allergic reactions as compared with isolated fragrance allergens. These results may explain why fragrance allergy is a prevalent phenomenon in spite of the fact that many fragrance allergens are categorized as weak sensitizers.…”
Section: Discussionmentioning
confidence: 99%
“…FM 1 and FM 2, not only reflect normal exposure to perfumes, but also provide the optimal stimulus to the immune system, and thereby have high diagnostic ability. Hence, in the light of the Bonefeld study, false‐negative reactions to the ingredients certainly also accounts for this phenomenon (33).…”
Section: Discussionmentioning
confidence: 99%
“…In the challenged skin the CTLs are activated and induce the inflammatory response. In a widely used animal model for contact hypersensitivity, mice are sensitized and challenged on the ears with haptens/allergens such as DNFB and the ensuing inflammatory response is then measured by determining the swelling of the ears 2931,40,41. To investigate the role of MID1 in CTL responses in vivo, we sensitized C57BL/6 and MID1 -/- mice with DNFB on their ears for three consecutive days and challenged them with DNFB on their ears three weeks later.…”
Section: Resultsmentioning
confidence: 99%
“…It has to be considered that such combinations may facilitate chemical penetration into the skin, thereby increasing local concentrations. In addition, the combination of contact allergens or of contact allergens and irritants may lead to synergistic or additive effects that amplify innate immune and stress responses ( Figure 1A,B) [45][46][47]. This may lead to sensitizations not observed with single compounds which can be explained mechanistically [48,49].…”
Section: Heterologous Innate Immune Stimulationmentioning
confidence: 99%